Demonstration Models of Teak and Aonla based Agroforestry in Eastern Up - Srivastav, Anubha; Tomar, Anita; Shukla, S. D. (International journal of Horticulture, Agriculture and Food science, 2023)
In view of importance and suitability of Teak and Aonla with different crop combinations, demonstration agroforestry models of these species were developed with the objectives to identify suitable seedling source of Teak and suitable variety of Aonla in different crop combinations for adoption by farmers of Eastern UP. Under model 1 of Aonla based agoforestry, It was found that increment in girth after two year of planting was highest (4.99 cm) for T 6 ( N -7 + agriculture) followed by T8 (chakaiya + agriculture, 4.70 cm) and other varieties with lowest (3.62 cm) value for T1 ( N6 control). On the basis of both height and girth data trends, variety N-7 performed well after two year of planting. Under model 2 in Teak based agroforestry , it was found that increment in girth after two year in T4 (tissue culture + agri) performed well (4.96 cm) after two year of planting followed by other varieties with lowest (3.91 cm) value for T1 . It can be concluded from results of different trials that preliminary trends showed that for Aonla, N7 (Neelam) variety is performing superior compared to other varieties of Aonla with crop combinations of potato, mustard and wheat . In case of Teak, seedlings of tissue culture origin is performing superior as compared to other treatments in crop combinations of gram, burseem and barley . No significant effect of intercropping on trees and crops was experienced in early data of growth parameters of trees and production yield of intercrops.